2020
DOI: 10.1002/jcla.23579
|View full text |Cite
|
Sign up to set email alerts
|

Elevated carcinoembryonic antigen and bronchial obstruction caused by a rotten vegetable leaf mimic lung cancer: A case report

Abstract: Tracheobronchial foreign body aspiration is a potentially risky medical event, associating with clinical manifestations varying from acute respiratory distress, to chronic pulmonary infections, even death. 1 Notably, accidental foreign body aspirations in children and adults with normal bronchial system are relatively uncommon occurrences, 2 which can develop with or without the presence of obvious incentives. Therefore, the condition often requires early detection and rapid intervention to improve respiratory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…CEA is considered a biomarker for SCLC and adenocarcinoma (AD) of the lung [29], and serum CEA is elevated in many types of cancers mostly in AD [30,31]. CEA is also increased in other types of non-cancerous diseases or other conditions [11,32]. Our results showed that high levels of CEA were observed in both NSCLC (which includes AD and SCC) and SCLC (Figures 1, 2A, 2B).…”
Section: Discussionmentioning
confidence: 56%
“…CEA is considered a biomarker for SCLC and adenocarcinoma (AD) of the lung [29], and serum CEA is elevated in many types of cancers mostly in AD [30,31]. CEA is also increased in other types of non-cancerous diseases or other conditions [11,32]. Our results showed that high levels of CEA were observed in both NSCLC (which includes AD and SCC) and SCLC (Figures 1, 2A, 2B).…”
Section: Discussionmentioning
confidence: 56%